Effect of silencing Bemisia tabaci TLR3 and TOB1 on fitness and begomovirus transmission - Thesnim, Pathukandathil; Jangra, Sumit; Kumar, Manish; Ghosh, Amalendu (Frontiers in Plant Science, 2023)
Bemisia tabaci (Hemiptera: Aleyrodidae) is one of the most important invasive pests worldwide. It infests several vegetables, legumes, fiber, and ornamental crops. Besides causing direct damage by sucking plant sap, B. tabaci is the principal vector of begomoviruses. Chilli leaf curl virus (ChiLCV, Begomovirus) transmitted by B. tabaci is a major constraint in chilli production. B. tabaci genes associated with metabolism, signaling pathways, cellular processes, and organismal systems are highly enriched in response to ChiLCV infection. The previous transcriptome study suggested the association of B. tabaci Toll-like receptor 3 (TLR3) and transducer of erbB2.1 (TOB1) in ChiLCV infection. In the present study, B. tabaci TLR3 and TOB1 were silenced using double-stranded RNA (dsRNA) and the effect on fitness and begomovirus transmission has been reported. Oral delivery of dsRNA at 3 µg/mL reduced the expression of B. tabaci TLR3 and TOB1 by 6.77 and 3.01-fold, respectively. Silencing of TLR3 and TOB1 induced significant mortality in B. tabaci adults compared to untreated control. The ChiLCV copies in B. tabaci significantly reduced post-exposure to TLR3 and TOB1 dsRNAs. The ability of B. tabaci to transmit ChiLCV also declined post-silencing TLR3 and TOB1. This is the first-ever report of silencing B. tabaci TLR3 and TOB1 to induce mortality and impair virus transmission ability in B. tabaci. B. tabaci TLR3 and TOB1 would be novel genetic targets to manage B. tabaci and restrict the spread of begomovirus.